Multicentric plasma cell variant of Castleman disease – A case reportMulticentric Plasma Cell Variant of Castleman Disease: A Case Report - Wilson, Anitha; Joseph, Elizabeth; Punnoose, Asha Peedikayil; Varghese, Minnu Elza; T, Ajmal (Annals of Pathology and Laboratory Medicine, 2024)
Castleman disease (CD) is a lymphoproliferative disorder with markedly different presentations and clinical courses. The manifestations of this rare disease depend on the distribution and pathologic subtype. The histological variants of CD include the hyaline vascular variant and the plasma cell variant, with the former constituting about 90% of cases. Clinically, the unicentric form of CD is associated with a better prognosis, while multicentric CD is linked to a long-term poor outcome with an increased risk of second malignancies. Histopathologic examination of the involved lymph nodes remains the mainstay of diagnosis due to the clinical heterogeneity of the disease. We present the case of a 64-year-old male who was evaluated for bilateral inguinal lymphadenopathy, with a PET scan showing multiple hypermetabolic intra-abdominal lymph nodes. In view of a strong clinical suspicion of lymphoma, excision biopsy of the left inguinal lymph node was performed and sent for histopathological examination.